CHARACTERIZATION AND ANTIPARASITIC ACTIVITY OF BENZOPHENONE THIOSEMICARBAZONES ON Trypanosoma brucei brucei - Georges C. Accrombessi; Jacques Poupaert; Raymond H. Fatondji; Salomé D. S. Kpoviessi; Fernand A. Gbaguidi; Bienvenu Glinma (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The structure of four synthesized thiosemicarbazones, substituted or not, of benzophenone has been confirmed by spectrometrical analysis IR, NMR 1H and 13C. Their anti-trypanosomal activities were evaluated on Trypanosoma brucei brucei. Among these compounds, benzophenone 4 phenyl-3-thiosemicarbazone 4 has the highest activity with the half-inhibitory concentration (IC50) = 8.48 micromolar (µM). Benzophenone 4-methyl-3-thiosemicarbazone 3 and benzophenone thiosemicarbazone 1 showed moderate anti-trypanosomal activity with IC50 values equal to 23.27 µM and 67.17 µM respectively. Benzophenone 2 methyl-3-thiosemicarbazone 2 showed no activity up to IC50 = 371.74 µM.